Efficient Derivation of Excitatory and Inhibitory Neurons from Human Pluripotent Stem Cells Stably Expressing Direct Reprogramming Factors. Issue 6 (8th June 2021) - Song, Saera; Ashok, Archana; Williams, Damian; Kaufman, Maria; Duff, Karen; Sproul, Andrew
Abstract: It is essential to generate isolated populations of human neuronal subtypes in order to understand cell‐type‐specific roles in brain function and susceptibility to disease pathology. Here we describe a protocol for in‐parallel generation of cortical glutamatergic (excitatory) and GABAergic (inhibitory) neurons from human pluripotent stem cells (hPSCs) by using the neurogenic transcription factors Ngn2 and a combination of Ascl1 and Dlx2, respectively. In contrast to the majority of neural transdifferentiation protocols that use transient lentiviral infection, the use of stable hPSC lines carrying doxycycline‐inducible transcription factors allows neuronal differentiation to be initiated by addition of doxycycline and neural medium. This article presents a method to generate lentivirus from cultured mammalian cells and establish stable transcription factor–expressing cell lines (Basic Protocol 1), followed by a method for monolayer excitatory and inhibitory neuronal differentiation from the established lines (Basic Protocol 2). The resulting neurons reproducibly exhibit properties consistent with human cortical neurons, including the expected morphologies, expression of glutamatergic and GABAergic genes, and functional properties. Our approach enables the scalable and rapid production of human neurons suitable for modeling human brain diseases in a subtype‐specific manner and examination of differential cellular vulnerability. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Lentivirus production and generation of stable hPSC lines Support Protocol 1 : Expansion and maintenance of hPSCs Basic Protocol 2 : Differentiation of EX‐ and IN‐neurons Support Protocol 2 : Experimental methods for validation of EX‐ and IN‐neurons